STUDY OF BUILDING FIRE EVACUATION AND GEOMETRIC MODELING BASED ON CONTINUOUS MODEL FDS+AVEC - Aristides Lopes da Silva (European Scientific Journal, ESJ, 2014)
It is true that high buildings under fire accident, many people begin to shock against each other due to the failure evacuation opportunity in the reduction of visibility due to the spread of smoke and other factors. Therefore causing a huge loss of life and property. Along with the evolution of hardware and software, the technique of numerical simulation has been widely applied in the simulation of reconstruction of fire, making it useful in the analyzes of the characteristics in the project to improve the speed of evacuation of occupants. So this article has in its focal point to interpret geometric modeling techniques suitable for future 3D simulations of the dynamics of the fire with a case study applied to a building of 20 floors in China with an area of 2060m2 (Technological Department of Wuhan University of Technology - Hubei, China) and the state of the art of this research topic. Some examples of geometric modeling scenarios for fire are vividly described, so as to introduce the study of the evacuation of fire in buildings based on the continuous model FDS+Evac.